PENGARUH DISKRIMINASI HARGA TERHADAP PENINGKATAN PENJUALAN KARTU PERDANA IM3 PADA PT. NUSAPRO TELEMEDIA PERSADA BOGOR - Hayati, Yetty Husnul; Hakim, Abdul Lukman (Universitas Pakuan, 2015)
ABSTRACTThe purpose of this study was to determine the effect of price discrimination on the level of prime IM3card sales at PT. Nusapro Telemedia Persada. This study on price discrimination and the level of primeIM3 card sales are done PT. Nusapro Telemedia Persada, using price data agency locations and pricesas well as increased sales of retail locations (IDR) on card products prime IM3. The analytical methodthat used is ranging from descriptive analysis using the formulas of multiple regression analysis, multiplecorrelation analysis, as well as testing hipotesis. Price discrimination prime IM3 card company PTNusapro Telemedia Persada is based on two indicators, namely: pricing Agent locations and pricing atretail locations. Application of the implementation of price discrimination on the IM3 SIM CardCompanies PT Nusapro Telemedia Persadais good enough. At company Telemedia Persada PT Nusaproaverage increase or decrease in sales of SIM cards IM3 in 2014 at 1,970,569,134. While the effect ofprice discrimination against prime IM3 card sales increase at company PT Nusapro Telemedia Persadaamounting to 68.3% and 31.7% influenced by other factors.Keywords: Discrimination Hara to increased sales